The Impact of Social Media Advertising on Customer Performance Using Logistic Regression Analysis - Sami Ali Obed; Dlshad Mahmood Saleh; Dashty Ismil Jamil (QALAAI ZANIST JOURNAL, 2023)
The purpose of this study is to analyze the impact of e-marketing on the situation of consumers Purchasing in Erbil, Kurdistan. It has been done quantitatively, employing straightforward random sampling. The data was collected through a survey of 340 social media users, who served as a sample using simple random sampling for selected these cases. The study variables include consumer purchase decisions as a dependent variable and social media advertising as an independent variable. As moderating variables, income, education, gender, age, and culture were all considered. The study's results show that social media advertising has a significant effect on consumers' purchase. Customers' wealth and education had little significant effect on the association between their consumers purchasing decisions and social media advertising, but gender, age, and culture of the consumers purchasing, source of income, and the COVID-19 pandemic (which has helped online shopping grow) all have significant moderating effects on consumers purchasing and advertising. This groundbreaking study examines how social media advertising affects customer purchasing behavior by examining the situation of consumers in Erbil City. Moreover, the outcomes of the data analysis using the SPSS statistical tool and Microsoft Excel.